2015
DOI: 10.1002/stem.2098
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Satellite Cells Undergo Myogenesis Under Basal Conditions and Are Required for Pharyngeal Muscle Maintenance

Abstract: The pharyngeal muscles of the nasal, oral, and laryngeal pharynxes are required for swallowing. Pharyngeal muscles are preferentially affected in some muscular dystrophies yet spared in others. Muscle stem cells, called satellite cells, may be critical factors in the development of pharyngeal muscle disorders; however, very little is known about pharyngeal satellite cells (PSC) and their role in pharyngeal muscles. We show that PSC are distinct from the commonly studied hindlimb satellite cells both transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 96 publications
(126 reference statements)
4
38
0
Order By: Relevance
“…It has long been speculated that satellite cells remain quiescent in their sublaminar niche until required for skeletal muscle repair ( 23 , 25 , 33 ). However, recent studies performed by Randolph et al ( 34 ) and Keefe et al ( 35 ) have demonstrated that satellite cells contribute nuclei to myofibers in adult muscles in sedentary mice, challenging this conventional view. Similarly, in the present study, satellite cell activity in 2-month-old rat skeletal muscle was detected under basal conditions, as evidenced by the presence of centrally-nucleated myofibers.…”
Section: Discussionmentioning
confidence: 98%
“…It has long been speculated that satellite cells remain quiescent in their sublaminar niche until required for skeletal muscle repair ( 23 , 25 , 33 ). However, recent studies performed by Randolph et al ( 34 ) and Keefe et al ( 35 ) have demonstrated that satellite cells contribute nuclei to myofibers in adult muscles in sedentary mice, challenging this conventional view. Similarly, in the present study, satellite cell activity in 2-month-old rat skeletal muscle was detected under basal conditions, as evidenced by the presence of centrally-nucleated myofibers.…”
Section: Discussionmentioning
confidence: 98%
“…Recent in vivo and in vitro studies indicate that pharyngeal satellite cells have unique biological characteristics compared to hindlimb satellite cells. Pharyngeal muscles contain increased numbers of activated and proliferating satellite cells and contribute new myonuclei to pharyngeal myofibers in the absence of induced injury ( Randolph et al, 2015 ). Additionally, in vitro clonal assays suggest a highly proliferative subpopulation of pharyngeal satellite cells could be contributing to the proliferative phenotype ( Randolph et al, 2015 ).…”
Section: Craniofacial Satellite Cells: Extraocular Masseter and Phamentioning
confidence: 99%
“…Pharyngeal muscles contain increased numbers of activated and proliferating satellite cells and contribute new myonuclei to pharyngeal myofibers in the absence of induced injury ( Randolph et al, 2015 ). Additionally, in vitro clonal assays suggest a highly proliferative subpopulation of pharyngeal satellite cells could be contributing to the proliferative phenotype ( Randolph et al, 2015 ). In vivo ablation studies indicated that satellite cells were required to maintain myonuclear numbers in certain pharyngeal muscles under basal conditions, suggesting that pharyngeal muscles undergo myonuclear turnover and require myonuclear addition from ongoing satellite cell myogenesis ( Randolph et al, 2015 ).…”
Section: Craniofacial Satellite Cells: Extraocular Masseter and Phamentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that satellite cells isolated from extensor digitorum longus (EDL) muscle, which originate from somite, differ in their fate-determination dynamics during proliferation, differentiation, and self-renewal compared with those from MAS muscle that originate from the cranial mesoderm (6). Satellite cells in the nasopharynx muscle of the head constitutively proliferate and contribute to myonuclear turnover without muscle injury (7), whereas these phenomena are rarely observed in limb muscles. The heterogeneity in the satellite cell population among muscles may therefore be related to region-specific pathophysiological phenotypes of muscle diseases (8).…”
Section: Introductionmentioning
confidence: 99%